Sound Energy Harvesting and Converting Electricity (SEHCE) - Mervin A Boco (Annals of Mathematics and Physics - Peertechz Publications, 2022)
The research study "Sound Energy Harvesting and Converting Electricity (SEHCE)" aims to create a better and easier way of producing another source of clean and renewable energy through sound. The study did not aim to be compared to other proven sources of electricity such as heat, wind, solar and hydroelectric, instead, it was created to find and explore new ways of producing an alternative source of energy. The project will undergo several processes such as designing, construction, testing, and evaluation. Through this, the researcher will be able to find out that sound energy can be converted to electricity.